2010
DOI: 10.1590/s0100-06832010000600019
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia dos contatos entre solo-saprolito-rocha em neossolos derivados de arenitos da formação caturrita no Rio Grande do Sul

Abstract: RESUMO(1) Recebido para publicação em janeiro de 2010 e aprovado em outubro de 2010.(2) Professor do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
8

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
4
0
8
Order By: Relevance
“…The data obtained for Alisols in the South of Brazil revealed that the C horizon should not be considered as saprolite as it does not show morphological or physical and chemical properties compatible with that layer, validating the results of Pedron et al (2009Pedron et al ( , 2010. In this study, the C horizon was identified according to clear evidence of a pedogenic process, which is not in agreement with the description found in the guides used to describe and classify soil profiles (Schoeneberguer et al, 2012;Santos et al, 2013;IUSS Working Group WRB, 2014;USDA, 2014).…”
Section: Boundary Between Soil and Saprolitesupporting
confidence: 74%
See 2 more Smart Citations
“…The data obtained for Alisols in the South of Brazil revealed that the C horizon should not be considered as saprolite as it does not show morphological or physical and chemical properties compatible with that layer, validating the results of Pedron et al (2009Pedron et al ( , 2010. In this study, the C horizon was identified according to clear evidence of a pedogenic process, which is not in agreement with the description found in the guides used to describe and classify soil profiles (Schoeneberguer et al, 2012;Santos et al, 2013;IUSS Working Group WRB, 2014;USDA, 2014).…”
Section: Boundary Between Soil and Saprolitesupporting
confidence: 74%
“…However, the tendency was reduction in the degree of wet consistency with depth; and transitions were smooth between the Bt and C horizons and irregular to wavy between the C horizons and Cr layers. Irregular and wavy transitions are common among less developed layers, as registered in the Cr layers, reflecting variability of alteration in the weathering processes (Stolt et al, 1993;Pedron et al, 2009Pedron et al, , 2010. Thus, although incipient, a major variation in the C horizon can be interpreted as resulting from pedogenetic processes.…”
Section: Identification Of the Boundary Between Soil And Saprolite Inmentioning
confidence: 97%
See 1 more Smart Citation
“…Apenas na estreita área plana que forma o fundo do enclave, onde as declividades foram menores, foi encontrado Neossolo Quartzarênico, com horizonte A assentado sobre horizonte C. Em ambos os solos, o material de origem é constituído de rochas sedimentares, sendo arenito o material mais frequente, em associação com argilitos e siltitos. Neossolos Litólicos e Neossolos Regolíticos derivados de rochas sedimentares ocorrem com certa frequência na região e conferem a esses locais um grau de fragilidade acentuada e de limitação para uso agrícola (PEDRON et al, 2010). Aproximadamente a 30km de distância do local do presente estudo, PEDRON et al (2010) O teor de MO encontrado foi baixo para os dois grupos fi tossociológicos em todos os intervalos de declividade (Tabela 1), o que pode estar relacionado com o material de origem arenítico e com a declividade acentuada da maior parte da área.…”
Section: Resultsunclassified
“…Neossolos Litólicos e Neossolos Regolíticos derivados de rochas sedimentares ocorrem com certa frequência na região e conferem a esses locais um grau de fragilidade acentuada e de limitação para uso agrícola (PEDRON et al, 2010). Aproximadamente a 30km de distância do local do presente estudo, PEDRON et al (2010) O teor de MO encontrado foi baixo para os dois grupos fi tossociológicos em todos os intervalos de declividade (Tabela 1), o que pode estar relacionado com o material de origem arenítico e com a declividade acentuada da maior parte da área. Solos derivados de materiais sedimentares não favorecem a adsorção de ácidos orgânicos, devido à baixa formação de complexo sortivo, fazendo com que o conteúdo orgânico seja rapidamente degradado pela atividade microbiana.…”
Section: Resultsunclassified